Peluang Revitalisasi Hukum Adat sebagai Sumber Kearifan Lokal : Potensi Pengembangan Ekonomi Lokal sebagai Upaya Kedaulatan Negara - Arief Fahmi Lubis (Universitas 17 Agustus 1945 Semarang, 2022)
The revitalization of customary law as a source of local wisdom does not mean returning to the past, but taking the essence of wisdom that has stood the test of time and adapting it to answer contemporary challenges. Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description when the research is carried out. The results of this study show that with the right approach, customary law can be a source of inspiration and solutions to various modern problems, ranging from environmental crises to erosion of social cohesion.